Insulin as a Bridge between Type 2 Diabetes and Alzheimer Disease – How Anti-Diabetics Could be a Solution for Dementia - Sebastião, Inês; Candeias, Emanuel; Santos, Maria S.; de Oliveira, Catarina R.; Moreira, Paula I.; Duarte, Ana I. (Frontiers in Endocrinology, 2014)
Type 2 diabetes (T2D) and Alzheimer disease (AD) are two major health issues nowadays. T2D is an ever increasing epidemic, affecting millions of elderly people worldwide, with major repercussions in the patients’ daily life. This is mostly due to its chronic complications that may affect brain and constitutes a risk factor for AD. T2D principal hallmark is insulin resistance which also occurs in AD, rendering both pathologies more than mere unrelated diseases. This hypothesis has been reinforced in the recent years, with a high number of studies highlighting the existence of several common molecular links. As such, it is not surprising that AD has been considered as the “type 3 diabetes” or a “brain-specific T2D”, supporting the idea that a beneficial therapeutic strategy against T2D might be also beneficial against AD. Herewith, we aim to review some of the recent developments on the common features between T2D and AD, namely on insulin signaling and its participation in the regulation of amyloid  (Aβ) plaque and neurofibrillary tangle formation (the two major neuropathological hallmarks of AD). We also critically analyze the promising field that some anti-T2D drugs may protect against dementia and AD, with a special emphasis on the novel incretin/glucagon-like peptide-1 receptor agonists.